2019
DOI: 10.1038/s41598-019-52640-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR for leprosy diagnosis and monitoring in household contacts: A follow-up study, 2011–2018

Abstract: Household contacts (HHC) of leprosy patients exhibit high-risk of developing leprosy and contact tracing is helpful for early diagnosis. From 2011 to 2018,2,437 HHC were examined in a clinic in Rio de Janeiro, Brazil and 16S qPCR was used for diagnosis and monitoring of contacts. Fifty-four HHCs were clinically diagnosed with leprosy at intake. Another 25 exhibited leprosy-like skin lesions at intake, 8 of which were confirmed as having leprosy (50% of which were qPCR positive) and 17 of which were diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 32 publications
4
33
0
1
Order By: Relevance
“…A longitudinal study conducted in Brazil (Manta et al, 2019), investigated SSS from 995 HHC by qPCR including follow-up for at least 3 years with occurrence of five new cases. The authors reported 20% qPCR positivity in HHC representing future new cases compared to 9% in HHC without disease.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study conducted in Brazil (Manta et al, 2019), investigated SSS from 995 HHC by qPCR including follow-up for at least 3 years with occurrence of five new cases. The authors reported 20% qPCR positivity in HHC representing future new cases compared to 9% in HHC without disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our clinic routinely performs diagnosis of difficult cases aided by the use of qPCR 28 . The availability of this method provides the clinicians the possibility to interrogate leprosy when histopathological analysis of prevalent contacts with smaller lesions examined at intake are assumed equivocal or inconclusive 13 , 28 . In Manta et al 13 we followed up 980 contacts for at least 3 years after diagnosis of the index cases.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, few studies have measured incidence in contacts from a follow-up cohort [12][13][14][15] . The factors associated with disease outcome among contacts include consanguinity, proximity, bacterial index/ clinical form of the index case, age, and sex 2,[12][13][14][15][16][17][18] .Contact tracing and geographic information systems studies reveal a concentration of new patients among household and social contacts, either children or adults, of previous patients highlighting the importance of developing differentiated actions for surveillance of this group [19][20][21] . Simulation studies 22 and systematic reviews 23 suggest that the control of leprosy could be achieved faster through household contact tracing associated with new interventions such as chemo or immunoprophylactic approaches 17,18,24 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past years, several studies have searched for biomarkers to (early) detect leprosy either based on the host immune response [26] , [27] , [28] , [29] , [30] , [31] , the pathogen [32] , [33] , [34] , [35] , [36] , [37] , or a combination of both [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] . Molecular detection by identification of the repetitive element RLEP by (quantitative) PCR [ 33 , 46 , 47 ] as well as detection of anti- M. leprae phenolic glycolipid I (PGL-I) IgM in blood [ 28 , 29 ] are methods employed to assist leprosy diagnosis.…”
Section: Introductionmentioning
confidence: 99%